МЕЙОБЕНТОС РІЗНИХ БІОТОПІВ ВЕРХНЬОЇ СУБЛІТОРАЛІ ОДЕСЬКОЇ ЗАТОКИ - Воробйова, Л.В. (Marine Ecological Journal, 2022)
In the article, for the first time for the shelf of the northwestern part of the Black Sea, the features of the formation total abundance and biomass of permanent (permanent members) and temporary (temporary members) components of meiobenthos in the upper sublittoral of the Odessa Bay (2.5–11 m). The material was presented by quantitative samples collected in 2012, in the coastal zone of the Odessa Bay. During the research period, from 9 to 13 groups of meiobenthos were found on various substrates: Foraminifera, Nematoda, Harpacticoida, Ostracoda, Halacaridae, Kinorhyncha, Turbellaria, Oligochaeta, larvae and juveniles of Polychaeta, Bivalvia, Gastropoda, Balanus. There are 9 large taxa on the sandy substrate, 12 on the shell, and 10 taxa on the stony substrate with algae cover. An analysis of the distribution of individual meiobenthic on various substrates showed their significant differences. Nematoda dominated on the sandy substrate. The main role was played by polychaetes and juvenile bivalves. On the shell rock, the total abundance of meiobenthos varied at different stations from 2500 ind. m-2 to 269000 ind. m-2 (average – 143300 ind. m-2), the main part of it was formed by eumeiobenthos (72.7 %). In the periphyton of rocky substrate, the meiobenthos consisted of 10 large taxons. Turbellaria, Kinorhyncha and Gastrotricha were absent. The total number of meiobenthos varied from 59000 ind. m -2 to 341000 ind. m -2 (on average 156107 ind. m -2). The proportion of eumeiobenthos in the total number of organisms was 67.4 %. On the mixed substrate, the formation of the total abundance of meiobenthos occurred mainly due to 6 groups (Nematoda, Harpacticoida, Ostracoda, Oligochaeta, Polychaeta, juveniles of Bivalvia). Concentration of the total meiobenthos varied from 83000 ind. m-2 to 146500 ind. m-2 (on average 120500 ind. m-2). Nematoda dominated, the subdominant group was Harpacticoida. The paper considers the formation of quantitative indicators of the main groups of meiobenthos (Foraminifera, Nematoda, Harpacticoida, Ostracoda, Halacaridae, temporary meiofauna) depending on the type of substrate.